Analysis Of Toddler Mother's Behavior Towards Diarrhea Disease Incidence (Case Study On Toddlers In Panekan Subdistrict, Magetan Regency Year 2024) - Dewanti, Dyah Ayu Villa; Suprijandani, Suprijandani; Setiawan, Setiawan; Nurmayanti, Demes (Poltekkes Kemenkes Semarang, 2025)
Panekan Community Health Center reported the highest number of diarrhea cases in Magetan Regency from 2021 to 2023, with incidence rates of 23,162 per 1,000 toddlers in 2021, 14,865 per 1,000 in 2022, and 12,703 per 1,000 in 2023. This study analyzed the behavior of mothers of toddlers regarding diarrhea incidence in the Panekan Community Health Center area in 2024. This study employed an observational analytical method with a cross-sectional approach, involving 27 mothers of toddlers selected from a population of 37 using proportional random sampling due to unequal population distribution across strata. Data were collected through interviews and observations and analyzed using the Chi-Square test. The results showed significant relationships between knowledge (p = 0.015), attitude (p = 0.000), belief (p = 0.000), habit (p = 0.000), family support (p = 0.000), and home sanitation facilities (p = 0.000) with diarrhea incidence. However, no significant relationships were found for health worker services (p = 1.000) and community support (p = 0.704). The study concluded that knowledge, attitude, belief, habit, family support, and home sanitation facilities significantly influenced diarrhea incidence. Mothers of toddlers are encouraged to participate in educational activities and counseling organized by the Panekan Community Health Center to improve their understanding of diarrhea prevention.